Seismic response modification factor for RC-frames with non-uniform dimensions. Issue 1 (1st January 2021) - Hussein, Manar M.; Gamal, Manar; Attia, Walid A.
Abstract: In existing seismic design codes, base shear is measured using the elastic force requirement divided by the strength reduction factor. This factor is used to take account of structures' ability to dissipate energy by inelastic deformations. The main objective of this study is to determine the response modification factor (R) for RC frames with non-uniform spans and heights and compare the values to the Egyptian Code of Practice ECP-201. The case study consists of three groups of RC frames with detailed structural design: uniform spans and heights, non-uniform spans, and non-uniform heights. A sum of 30 systems of frames is analyzed by nonlinear static analysis, "pushover analysis, " using SAP2000 with FEMA-356 provisions to assess the R factor. Also, a comparison is held with R factor in the Egyptian code. It was found, considering the limitations mentioned in the conclusions, that R factor decreases with increasing the height of selected floors and it is greatly affected by the non-uniformity of span lengths. The listed values of R factor in the Egyptian code are conservative and not economic. Thus, it is recommended to include the non-uniformity in spans and heights, to get more accurate values of R factor.